Rapid Syntheses of (−)‐FR901483 and (+)‐TAN1251C Enabled by Complexity‐Generating Photocatalytic Olefin Hydroaminoalkylation. (30th December 2019) - Reich, Dominik; Trowbridge, Aaron; Gaunt, Matthew J.
Abstract: We report a common strategy to facilitate the syntheses of the polycyclic alkaloids (−)‐FR901483 (1 ) and (+)‐TAN1251C (2 ). A divergent synthetic strategy provides access to both natural products through a pivotal spirolactam intermediate (3 ), which can be accessed on a gram‐scale. A photocatalytic olefin hydroaminoalkylation brings together three readily available building blocks and forges the majority of the carbon framework present in 1 and 2 in a single operation, leading to concise total syntheses. The complexity‐generating photocatalytic process also provides direct access to novel non‐racemic spirolactam scaffolds that are likely to be of interest to early‐stage drug discovery programs. Abstract : Kurz und bündig : Die Synthese der polycyclischen Alkaloide (−)‐FR901483 und (+)‐TAN1251C über ein gemeinsames Spirolactam‐Intermediat wird vorgestellt. Photokatalytische Olefinhydroaminoalkylierung vereinigt drei leicht erhältliche Bausteine und produziert den Großteil des Kohlenstoffgerüsts in einem Schritt, was zu kurzen und bündigen Totalsynthesen führt.